A Preliminary Study on the Barriers in Listening Section of English Proficiency Test: Students’ Perspectives - Paulina paulina; Farah Natchiar Mohd Khaja; Abdul Ghani Abu (Universitas Muhammadiyah Gresik, 2022)
Abstract This study intends to find out the problems or barriers faced by Indonesian students in studying for an English proficiency test (EPT), especially in Listening section. EPT becomes a standard English test and a compulsory test for students since it is used as one of the requirements for their graduation at the degree level, and also for a job application. Those requirements increase the demand of the test. However, the fact shows that the test takers of the EPT took the test for times since they cannot pass the targetted score. This fact led this study to investigate further about the barriers they face in EPT. The study also describes kinds of English Proficiency Test and the kind used in University of Muhammadiyah Gresik. The design of the study is descriptive qualitative with 40 students as the subject. The data will be collected from questionnaire and follow-up interview to answer the question and reveal the barriers they face during the test.